Enacting critical care and transformative leadership in schools highly impacted by poverty: an African-American principal's counter narrative. Issue 5 (19th October 2016) - Wilson, Camille M.
Abstract : Critical notions of care and transformative educational leadership are much aligned, yet they are rarely simultaneously addressed in research. This article highlights the benefits of transformative educational leadership that enacts critical care. Critical care involves embracing and exhibiting values, dispositions and behaviours related to empathy, compassion, advocacy, systemic critique, perseverance and calculated risk-taking for the sake of justly servfing students and improving schools. Data discussed stem from the in-depth interviews of an African-American principal who implemented such practices and consequently helped boost the academic performance of a school highly impacted by poverty. The principal's accounts of her practice comprise a counter narrative reflective of critical race methodology. Findings from the study speak to the importance of educators better understanding the reality of poverty given racialized conditions and other oppressive contexts so they can better prepare marginalized youth to achieve and succeed.